Testing water banking recovery policies to secure drought water supply in semi-arid areas with a changing climate - Peter Dillon; Bridget R. Scanlon; Rebecca Bernat; Dennis Gonzalez; Constantin Seidl; Declan Page; Rebecca Doble; John Radcliffe; Adam Hutchinson; Sharon B. Megdal (Groundwater for Sustainable Development, 2026)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Increasing In-Row Spacing Enhances Potato Virus Y and Potato Leafroll Virus Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale; Ian MacRae (American Journal of Potato Research, 2015)

Resistance to Aphids, Late Blight and Viruses in Somatic Fusions and Crosses of Solanum tuberosum L. and Solanum bulbocastanum Dun - Jeffrey A. Davis; Edward B. Radcliffe; Christian A. Thill; David W. Ragsdale (American Journal of Potato Research, 2012)

Planter Skips and Impaired Stand Favors Potato Virus Y Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2009)

Border Treatment to Reduce Insecticide Use in Seed Potato Production: Biological, Economic, and Managerial Analysis - Matthew W. Carroll; Edward B. Radcliffe; Ian V. MacRae; David W. Ragsdale; Kent D. Olson; Thaddee Badibanga (American Journal of Potato Research, 2009)

Resistance to green peach aphid,Myzus persicae (Sulzer), and potato aphid,Macrosiphum euphorbiae (Thomas), in potato cultivars - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2007)

Soybean aphid,Aphis glycines Matsumura, a new vector ofPotato virus Y in potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2005)

Aphid-transmitted potato viruses: The importance of understanding vector biology - Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2002)

Genetic Resistances to Potato Leafroll Virus, Potato Virus Y, and Green Peach Aphid in Progeny ofSolanum etuberosum - R. G. Novy; A. Nasruddin; D. W. Ragsdale; E. B. Radcliffe (American Journal of Potato Research, 2002)

RAPD analysis of genetic diversity inSolanum populations to predict need for fine screening - J. B. Bamberg; C. Singsit; A. H. del Rio; E. B. Radcliffe (American Journal of Potato Research, 2000)

Potato fungicides interfere with entomopathogenic fungi impacting population dynamics of green peach aphid - Abdelaziz Lagnaoui; Edward B. Radcliffe (American Journal of Potato Research, 1998)

Geographic distribution of insect resistance in potatoes - Kathy L. Flanders; Edward B. Radcliffe; John G. Hawkes (Euphytica, 1997)

Fine screeningSolanum (potato) germplasm accessions for resistance to Colorado potato beetle - J. B. Bamberg; C. A. Longtine; E. B. Radcliffe (American Journal of Potato Research, 1996)

Potato leafroll virus spread in differentially resistant potato cultivars under varying aphid densities - Christina D. DiFonzo; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1995)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Breeding behavior of resistance to green peach aphid in tuber-bearing Solanum germplasm - D. W. Sams; F. I. Lauer; E. B. Radcliffe (American Journal of Potato Research, 1976)